Clinical Outcomes of the Ilizarov Method After an Infected Tibial Non Union - Shahid, Mohammad (Kowsar, 2013)
BACKGROUND: The Ilizarov technique has been used in the UK for the last 20 years in the management of infected non-union of long bones. This method uses fine wires inserted percutaneously which are attached and tensioned to provide a strong frame construct. The majority of tibial and femoral non unions can be treated successfully by internal fixation. However, an infected non-union of the tibia can prove a difficult problem. The Ilizarov method can prove useful for treating these complex injuries. OBJECTIVES: To assess whether a new limb reconstruction centre in the UK has comparable results. PATIENTS AND METHODS: Twelve patients (10 M: 2 F; Avg age 43.3 years) who had an infected tibial non-union between March 2009 and August 2010 treated with the Ilizarov technique. Intervention method was Ilizarov technique and main outcome measures include functional and radiological outcomes assessed using the Association for the Study and Application of Methods of Ilizarov (ASAMI) criteria, American Orthopaedic Foot and Ankle Score (AOFAS) and Visual Analogue Pain scores. RESULTS: All twelve patients united. None required amputation. Mean time to union was 46 weeks (range 24 - 70/median 50). The average follow up time was 62 weeks (39 - 164/ median 59). According to the ASAMI score bone/radiological results ten were classed as excellent with the remainder being good. Functionally six were graded as excellent, four as good and two as poor. The average AOFAS score was 83/100 (70 - 90) and pain visual analogue scale (VAS) was two. CONCLUSIONS: Our results in terms of ASAMI scores are comparable with the published literature. Furthermore, our return to work is better than most European studies (63%). All our patients said they would have the procedure again. We attribute this success partly to the multidisciplinary approach. We recommend early referral to a dedicated unit if there is any evidence of a non-union.